High-resolution study of selected Dansgaard- Oeschger events and Heinrich event 4 42,189–33,393 cal. years BP. Gravity core JM11-FI-15GC from Fugløy Ridge, northeastern Faeroe Islands Margin - Jónsdóttir, Björg (UiT Norges arktiske universitet, 2015)
The focus of this thesis was selected Dansgaard-Oeschger (D-O) events and Heinrich event 4 (H4). A gravity core, JM11-FI-15GC, from Fugløy Ridge was used for the investigation. The location of the core site is important due the fact that the Faeroe- Shetland Channel is a key area in understanding the changes in circulation during the last glacial period. In total there were eighteen D-O climatic events found within the investigated core. Only part of core JM11-FI-15 GC was used, which is dated to between 42,189 – 33,393 cal. years BP. It is a short interval, comprising a total of four D-O climatic events, which were studied in high-resolution. The events were correlated to the NGRIP ice-core using interstadials and tephra layer FMAZ-III as tie points. The largest D-O event was used as a template, for smaller events, when the data was interpreted. The D-O event was further subdivided into three intervals based on oxygen isotopes, magnetic susceptibility, concentration of planktic foraminifera and ice rafted detritus. Interstadial intervals had similar circulation as today, with formation of North Atlantic Deep water (NADW). These intervals started abruptly after the colder stadials. Transitional cooling intervals were characterized by reduction in the formation of NADW, with increasing concentration of ice rafted detritus. There was indication that the environment was unstable. During Heinrich event 4 the formation of NADW was either greatly reduced or had stopped. There was high concentration of IRD and increased melt water from icebergs as indicated by low δ18O values. High concentration of the benthic foraminiferal species C. neoteretis indicated the presence of the Atlantic Intermediate water. Fragmentation of foraminiferal tests was used track changes in dissolution. There was low dissolution during the stadials, which was likely caused by low organic productivity. The dissolution obscured the data, indicating the stadials were characterized by warmer surface water then interstadials.